Kate: A Voice to Sexual Abuse Trauma in Helen Benedict’s Sand Queen - Intisar Rashid Khaleel (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
war trauma and its relationship to women in regions of conflict are conceptualized by the confusion of identities between male and female identity, soldiering, and even immigration issues. The majority of combat literature has been written by men, but Sand Queen distinguishes apart because it emphasizes the viewpoint of the female character and author. The story of Kate develops to depict the gruesome details and complexities of the conflict. Her experience demonstrates that women face particular challenges throughout combat as well as in civilian life. In Sand Queen, the consequences of the war trauma can be seen in the characters' reactions throughout the dialogical narrative that recounts the terrible experiences of a female soldier.